Community Empowerment through Participatory Training for Sustainable Nile Tilapia Farming in Tanjung Alam, Asahan Regency - Rumondang, Rumondang; Suriono, Hadi; Ramadhan, Muhammad Sabir; Fransiska, Adelia; Fitri, Kurnia Aidila; Putri, Zeini Ardianti; Ningrum, Hesti Sulistia; Tambunan, Syafrida Br; Nurhadi, Nurhadi (Media Publikasi Cendekia Indonesia, 2025)
The cultivation of Nile tilapia (Oreochromis niloticus) is a strategic initiative to promote aquaculture development in Indonesia and to enhance economic welfare by providing sustainable income opportunities. This community empowerment program was implemented with the Sudo Mina Jaya Fish Farmers Group in Tanjung Alam Village, Asahan Regency, aiming to strengthen farmers’ capacity and technical skills through a participatory approach. Key challenges identified included inadequate water quality management, limited knowledge of breeding techniques, and issues affecting fish health and productivity. The program employed the Participatory Rural Appraisal (PRA) method, comprising an initial survey, training on sustainable tilapia breeding, pond management, and probiotic production, as well as technical assistance and interactive guidance sessions. Program effectiveness was evaluated using pre-test and post-test assessments. Results showed a significant increase in participants’ knowledge scores from a mean pre-test score of 54 to a post-test mean of 92 (n = 13), confirmed by a Wilcoxon signed-rank test (Z = 3.209, p = 0.001). Continued technical assistance and regular monitoring further supported the practical application of the knowledge gained. This program successfully provided practical solutions to local challenges, enhanced participants’ aquaculture skills, and opened opportunities for sustainable fish farming businesses